2018
DOI: 10.1063/1.5022371
|View full text |Cite
|
Sign up to set email alerts
|

The influence of titanium adhesion layer oxygen stoichiometry on thermal boundary conductance at gold contacts

Abstract: We experimentally demonstrate the role of oxygen stoichiometry on the thermal boundary conductance across Au/TiO x /substrate interfaces. By evaporating two different sets of Au/TiO x / substrate samples under both high vacuum and ultrahigh vacuum conditions, we vary the oxygen composition in the TiO x layer from 0 x 2.85. We measure the thermal boundary conductance across the Au/TiO x /substrate interfaces with time-domain thermoreflectance and characterize the interfacial chemistry with x-ray photoemission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…The best fit for κ PMMA and G for the three different systems are summarized in the Table 2 The G values are within the same order of magnitude as experimental and theoretical values reported by others [8,20,33,34]. The ATPS sample sees a near doubling in G. The increase in G is in agreement with recent work where TiO x with near-zero oxygen content acted as thermal management at Au/non-metal interfaces [35]. Duda et al reported that the thermal boundary conductance at Au/Si interface was enhanced by a factor of four by inclusion of a Ti adhesion layer and removal of the native oxide [10].…”
Section: Resultssupporting
confidence: 87%
“…The best fit for κ PMMA and G for the three different systems are summarized in the Table 2 The G values are within the same order of magnitude as experimental and theoretical values reported by others [8,20,33,34]. The ATPS sample sees a near doubling in G. The increase in G is in agreement with recent work where TiO x with near-zero oxygen content acted as thermal management at Au/non-metal interfaces [35]. Duda et al reported that the thermal boundary conductance at Au/Si interface was enhanced by a factor of four by inclusion of a Ti adhesion layer and removal of the native oxide [10].…”
Section: Resultssupporting
confidence: 87%
“…For Au/Ti/Gr/SiO 2 without any surface functionalization, an intrinsic h K ≈33 MW m −2 K −1 has been measured that is four times smaller than that of the Au/Ti/SiO 2 interface . Recent studies have also shown that h K measured across Au/Ti/Gr/SiO 2 and Au/TiO x /substrate interfaces are not only impacted by the weak interfacial bonding, but are also significantly impacted by the oxide compositions at the Ti contacts that are highly dependent on the Ti deposition rate and base pressure …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…[161] Recent studies have also shown that h K measured across Au/Ti/Gr/SiO 2 and Au/TiO x /substrate interfaces are not only impacted by the weak interfacial bonding, but are also significantly impacted by the oxide compositions at the Ti contacts that are highly dependent on the Ti deposition rate and base pressure. [162,163]…”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…While there are pre-existing measurements on the effect of different metal compositions on G, [8][9][10] the outstanding research questions that this work addresses are how temperature treatment affects the interdiffusion of metal bilayer films on dielectric substrates, and how this interdiffusion affects G. Our experiments focus on interdiffusion of the Au-Cu adhesion layer system, and are compared to several published studies [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%